Morphological analysis in comparison - Dressler, Wolfgang U., 1939- (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 2000)
This volume consists of selected and revised papers from the Seventh International Morphology Meeting, held in 1996 in Vienna. It presents advances in morphological theorizing, such as the foundations of sign-based morphology, the morphology-syntax interface, the boundaries between compounding and derivation, derivation and inflection, and the emergence of morphology from premorphological precursors in early first-language acquisition. The contributions deal with morphological analyses in various fields of the ever-widening domain of morphology and its relevance to the lexicon. The compa.